The State of Responsibility to Protect Inception in ASEAN Regionalism - Muhammad Rum (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
As a regional organization, ASEAN upholds its core principles of non-interference, consultation and consensus. Meanwhile, Responsibility to Protect (R2P) encourages the need for the international community’s intervention to a country that falls to its citizens. Hence, this creates tension between ASEAN principles and R2P. The tension is reflected when the limited capacity of a member state’s government might invite humanitarian intervention from the international community. This research aims to discuss how Southeast Asian regionalism adapts to this situation and is undergoing dynamic reformulation to reconcile ASEAN Way and humanitarian principles. In contemporary Southeast Asian Studies, the extent of R2P inception in ASEAN regional cooperation is understudied. These methods utilize a reductionist approach in I.R. studies by explaining ASEAN through the analysis of individual actors based on a constructivism school of thought. The data taken from the interviews are utilized to confirm ASEAN and member states’ positions. This study argues that the traditional constructivist tipping point measurement for an international norm needs to be revisited. The tipping points for R2P in international forums may not necessarily be well-reflected at the regional level.